Cultural correlates of depression among Turkish immigrant and German women: implications for psychotherapeutic practice with Turkish immigrants - Balkir, Nazli (2012)
Germany is characterized by hosting a growing number of populations from various divergent ethnic backgrounds and recently immigrants constitute nearly eight percent of the whole population. An increasing number of research reports strong association between immigrant status and psychopathology as well as results indicating different prevalence rates of psychiatric disorders among divergent ethnic groups. This highlights the issues regarding cultural differences in etiology, utilization of mental health services and biases in diagnostics/treatment outcomes. Undeniably, a structured framework in which universal and cultural determinants of mental health are integrated is necessary to gather a complete understanding of the picture. Therefore, the current dissertation explored and integrated universal patterns of and cultural variations in (a) the interaction between emotion regulation strategies and its affective and cognitive consequences, (b) explanatory models of depression, models for help-seeking behaviour, treatment outcomes, and social response to mental illness. Quantitative and qualitative methods were used to investigate first generation immigrants from Turkey and German women with and without depression.
Keywords: Hochschulschrift